Speed and fatigue control using speed limiter integrated fatigue analyzer for truck and bus - Pranoto, Hadi (2020)
Developing country such as Indonesia reported that from total 6,231 road traffic crashes, over 85% of deaths, and close to 90% of disability in 2015. Large number of road traffic victims were due to by several factors such as external (34%), attitude (24%), fatigue (20%), over speed (17%) and vehicle technical problem such as maintenance short falls (5%). The main objective of this study is to develop the speed limiter that integrated with fatigue analyser and investigate its effect on engine performance, accident rate and user (driver and passenger) perception. The new features were developed through several stages which include determining parameters such as frequency and voltage, speed, driver fatigue parameter by Eye Aspec Ratio (EAR), Mouth Aspec Ratio (MAR) and Heart Rate (HR). The parameters used to formulate the driver Sleepiness Scale (SS), simulation of electronic components, features fabrication, testing and analysis. A device with new features named Speed Limiter Integrated Fatigue Analyzer (SLIFA) was applied and monitored in two transportation companies in Indonesia, namely PT. Pertamina Persero and PT. Pahala Kencana. The monitoring was conducted for one year for pre and post installation of SLIFA. The results showed that after installing the SLIFA, the average speed was succesfully reduced to 70 km/h for truck and 90 km/h for bus. In fatigue detection, the driver reached high EAR of 0.5, MAR of 1.6, HR scale of 95 bpm and high SS of 5.55. Engine performance and fuel consumption analysis showed that SLIFA had no effect in reducing the engine performance nor fuel consumption. As for the accident rate before installing the SLIFA, 51 accident cases were recorded, and after SLIFA installation, only 27 accident cases were recorded. This means that SLIFA was very useful in reducing accident by 47%. Based on satisfaction analysis using questionnaire conducted on the user, regression coefficient of 91.7% indicating a positive remark. Thus, SLIFA is acceptable and recommended to be installed and be marketed.